2017
DOI: 10.1515/anre-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation of upper long bones by selected measurements in a Radom (Poland) population from the 18th and 19th centuries AD

Abstract: Several studies have shown that sex estimation methods based on measurements of the skeleton are specific to populations. Metric traits of the upper long bones have been reported as reliable indicators of sex. This study was designed to determine whether the four long bones can be used for the sex estimation of an historical skeletal population from Radom (Poland). The material used consists of the bones of 169 adult individuals (including 103 males and 66 females) from the 18th and 19th centuries. Twelve meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…16 Likewise, in 2017, amongPoland population with the accuracy of gender estimation by radial length was 84 %. 17 Other long bone such as humerus was also reported to predict gender with the accuracy of 93.3% in an Egyptian sample. 18 Gender prediction has also been calculated by femur dimensions with the accuracy of 72.5% in males, and 85% in females.…”
Section: Discussionmentioning
confidence: 93%
“…16 Likewise, in 2017, amongPoland population with the accuracy of gender estimation by radial length was 84 %. 17 Other long bone such as humerus was also reported to predict gender with the accuracy of 93.3% in an Egyptian sample. 18 Gender prediction has also been calculated by femur dimensions with the accuracy of 72.5% in males, and 85% in females.…”
Section: Discussionmentioning
confidence: 93%
“…However, the level of accuracy was only 86.5% for complete radius from South African samples whereas the incomplete radius resulted in 86% of accuracy [9]. In addition, the accuracy of sex estimation function using radius from Indian and archaeological Polish population was less than 90% [9,11,13]. The discrepancy might be caused by the variation across different populations, in which differential environmental and genetic factors affect the degree of sexual dimorphism expression in each population [19].…”
Section: Discussionmentioning
confidence: 98%
“…In 2001, Mall et al [7] stated that radius performed the best among the three upper limb bones in sex estimation of samples from the contemporary German population. Similarly, previous studies also highlighted that the radius showed high degree of sexual dimorphism, and its dimensions could be used for estimating sex with high classification rates across many populations [6][7][8][9][10][11][12][13]. For instance, the antero-posterior diameter of the radial mid-shaft could predict the sex with the accuracy of 90.4% in the Indian population [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, femoral measurements provided an accuracy of 90.2% in North Indians (Srivastava et al, 2012), 94.2% in Thais (King et al, 1998), and 92.3% in Chinese (İşcan & Shihai, 1995), while tibial measurements resulted in 88% accuracy in a pooled South European assemblage consisting of Greek, Italian, and Spanish individuals (Kranioti & Apostol, 2015). Finally, combinations of upper limb long bone measurements reached correct sex discrimination accuracies of 90.3%–95.7% in modern Greeks (Charisi et al, 2011), but only 83%–84% in a Polish group (Tomczyk et al, 2017) and various long bone measurements from the upper and lower limbs reached accuracies of sex determination from 91% to 95% in a Japanese assemblage (Sakaue, 2004).…”
Section: Discussionmentioning
confidence: 98%